Computer Integrated Flexibile Manufacturing Cell - Zenobia Weiss (Communications - Scientific letters of the University of Zilina, 2000)
The paper describes the flexible manufacturing cell (FMC) created in INCO-Copernicus Project. „Product and Process Data Modelling for FMC - PPDM-MC“ (CP-960052). The FMC is integrated with computer systems as: CAD, CAD/CAM, PPC and SFC, which makes the flow of information possible between them and the demonstration of the full manufacturing cycle in the FMC. In the flexible manufacturing cell rotating and prismatic parts can be manufactured. Using simulation devices FACTOR AIM and Roans enables to make simulation experiments, which provide the data for optimisation of product and process data design in FMC.